An experimental and numerical analysis of residual stresses in a TIG weldment of a single crystal nickel-base superalloy - Chen, J; Salvati, E; Uzun, F; Papadaki, C; Wang, Z; Everaerts, J; Korsunsky, AM (Elsevier, 2020)
The Tungsten Inert Gas (TIG) welding technique is extensively used to join various automobile and aerospace components, such as control arms, rotating blades, and vanes. Highly localized heating followed by rapid cooling during welding exert complex thermal and mechanical loading on the components and give rise to significant residual stress fields which may increase the likelihood of time-dependent failure by promoting crack initiation. In the context of engineering design for structural integrity and reliability of operation, quantitative residual stress evaluation in the finished parts needs to be carried out in a reproducible manner. Samples investigated in this study were TIG fill-in weldments in single crystal superalloy components with nearly cylindrical geometry. The present research employed Focused Ion Beam – Digital Image Correlation (FIB-DIC) micro-ring-core technique for stress evaluation, and a sequentially coupled thermo-mechanical finite element model to assess the residual stress state near the weldment surface in the radial and hoop directions. Good agreement was obtained between experimentally evaluated residual stresses and the refined numerical predictions. The highest hoop and radial tensile residual stresses were both observed near the boundary between the filler metal and base metal, whilst a compressive region was found for hoop stress in the parent metal at the component edge. These observations were discussed in conjunction with the temperature history and residual stress self-equilibration. This research provides the foundation for further investigations of Post Weld Heat Treatment (PWHT) and surface treatment to improve the fatigue performance of weldments.